Escreva na forma ax² + bx + c = 0 a equação 15x² - 8 + 12x = 6x + 12x² - 6.
Soluções para a tarefa
Respondido por
1
15x^2 - 8 + 12x = 6x + 12x^2 - 6
15x^2 - 12x^2 - 8 + 12x = 6x - 6
3x^2 - 8 + 12x = 6x - 6
3x^2 - 8 + 6 + 12x = 6x
3x^2 - 2 + 12x = 6x
3x^2 - 2 + 12x - 6x = 0
3x^2 - 2 + 6x = 0
3x^2 - 2 + 6x = 0
Perguntas interessantes
História,
7 meses atrás
Geografia,
7 meses atrás
Português,
8 meses atrás
Matemática,
8 meses atrás
Matemática,
1 ano atrás
Filosofia,
1 ano atrás
Matemática,
1 ano atrás